Kinetic model for adherent Vero cell growth and poliovirus production in batch bioreactors. (June 2019) - Jiang, Yang; van der Welle, Joyce E.; Rubingh, Olaf; van Eikenhorst, Gerco; Bakker, Wilfried A.M.; Thomassen, Yvonne E.
Graphical abstract: Highlights: Mathematical model for Vero cell growth in batch bioreactors. Mathematical model for poliovirus proliferation on Vero cells. Oxygen uptake rate as process analytical technology for simple process monitoring. Abstract: The production of poliovirus vaccines in adherent Vero cells in batch bioreactors usually consists of a two-step upstream process: (1) Vero cell cultivation on microcarriers and (2) poliovirus proliferation. In this study we developed a mathematical model to describe this two-step process. We introduced the calculation of the oxygen uptake rate (OUR) and a correction of measurement for the sampling effect in order to ensure the high quality data sets. Besides the data of the OUR, we selected glucose concentration, Vero cell concentration and the virus titer for daily in process control to evaluate the progress of the process. With the selected data sets, the described model can accurately describe poliovirus production by Vero cells. Several other regular in process control samples (e.g. lactate concentration, ammonia concentration, and amino acids concentration) were excluded from the model, simplifying the process control analysis and minimizing labor.